Beauty in chemistry: A self-organized and dual-phase emissive diketopyrrolopyrrole derivative as high-yield fluorescent material. (October 2021) - Yang, Qingying; Sun, Xinyu; Han, Jianwei; Wang, Limin
Abstract: In the long-span human history, "beauty" has always been the ultimate pursuit of mankind's civilization. In this work, we report the synthesis of a beautiful fluorescent material based on an old-brand pigment named diketopyrrolopyrrole (DPP) with a high yield up to 90%. The completely overlapping molecules, which in general case would cause aggregation-induced quenching (ACQ) effect, can unexpectedly emit in both solvent and solid state (solid-state fluorescent quantum yield up to 30%). The term "beauty" has been verified by various types of optical spectra, while luminescence mechanism is systematically investigated by single-crystal X-ray diffraction (XRD), time-dependent density functional theory (TD-DFT) calculation and concentration-dependent absorption/emission. A self-organization process is observed. The promising future for large scale production can be foreseeably met by its quick synthesis and satisfied yield. Highlights: Various types of optical measurement were taken to define the beauteousness in a valid and rigorous manner. Mechanism study was conducted to understand how packing pattern can relate to bulk material's appearance. The target product is emissive in both solvent and aggregate state, with a considerably high solid-state Φf of 30%. The product yield can reach 90%, allowing a promising future for large-scale production.